Examining the potential of floating car data for dynamic traffic management. Issue 5 (19th February 2018) - Houbraken, Maarten; Logghe, Steven; Audenaert, Pieter; Colle, Didier; Pickavet, Mario
Abstract : Traditional traffic monitoring systems are mostly based on road side equipment (RSE) measuring traffic conditions throughout the day. With more and more GPS‐enabled connected devices, floating car data (FCD) has become an interesting source of traffic information, requiring only a fraction of the RSE infrastructure investment. While FCD is commonly used to derive historic travel times on individual roads and to evaluate other traffic data and algorithms, it could also be used in traffic management systems directly. However, as live systems only capture a small percentage of all traffic, its use in live operating systems needs to be examined. Here, the authors investigate the potential of FCD to be used as input data for live automated traffic management systems. The FCD in this study is collected by a live country‐wide FCD system in the Netherlands covering 6–8% of all vehicles. The (anonymised) data is first compared to available road side measurements to show the current quality of FCD. It is then used in a dynamic speed management system and compared to the installed system on the studied highway. Results indicate the FCD set‐up can approximate the installed system, showing the feasibility of a live system.